2019
DOI: 10.3390/ma12101595
|View full text |Cite
|
Sign up to set email alerts
|

Quenching Sensitivity of Al-Zn-Mg Alloy after Non-Isothermal Heat Treatment

Abstract: Type Al-Zn-Mg alloy has a wide ranges of application in vehicles, but corrosion resistance and mechanical properties of this alloy after heat treatment or heat straightening limits its utilization. This paper investigates the effect of quenching condition during non-isothermal heat treatment on corrosion behavior and mechanical properties of Al-Zn-Mg alloy. The corrosion resistance of Al-Zn-Mg alloy decreases after non-isothermal heat treatment and the sample after air quenching has the lowest corrosion resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…The R ct is usually used to evaluate the sensitivity, and the smaller R ct value represents a higher corrosion current density and thus a worse corrosion resistance [ 23 ]. The R ct of the weld zones in ER5087 and ER5356 weld joints gradually decreased with the increase of NaCl concentration, indicating that the surface activity of the two kinds of weld zones increased correspondingly, and the corrosion inhibition ability decreased.…”
Section: Resultsmentioning
confidence: 99%
“…The R ct is usually used to evaluate the sensitivity, and the smaller R ct value represents a higher corrosion current density and thus a worse corrosion resistance [ 23 ]. The R ct of the weld zones in ER5087 and ER5356 weld joints gradually decreased with the increase of NaCl concentration, indicating that the surface activity of the two kinds of weld zones increased correspondingly, and the corrosion inhibition ability decreased.…”
Section: Resultsmentioning
confidence: 99%
“…An ultimate yield strength of 582 MPa was obtained when an Al-5.87Zn-2.07Mg-2.42Cu alloy was cooled to 140 • C. Guo et al [21] showed that the corrosion resistance of 7N01 aluminum alloy improved after non-isothermal aging, and the maximum aging temperature (Tmax) significantly affected the mechanical properties. Li et al [22] found that the corrosion resistance of Al-Zn-Mg alloy was improved when subjected to 5 min of air cooling, followed by water quenching after non-isothermal aging. Peng et al [23] investigated the non-isothermal aging of 7050 alloy and found that the hardness and tensile strength improved to 182 HV and 578 MPa as the aging progressed.…”
Section: Introductionmentioning
confidence: 99%
“…Quenching needs to proceed with an extremely fast cooling rate to retain more solute atoms and vacancies, which are a prerequisite of further strengthening treatment like artificially aging, so that it can determine the effects of the precipitation strengthening [2]. If the cooling rate during quenching is relatively low, the strength and hardness cannot reach the best condition in the following aging treatment [3]. Conversely, the large quenching rate may cause greater residual stress and grain deformation, which may lead to the deformation and even cracking of the alloy.…”
Section: Introductionmentioning
confidence: 99%